China and the birth of globalization in the 16th century - Flynn, Dennis Owen (Variorum collected studies series, 2010)
This work is split up into four parts. These are 'Overviews', 'The Pacific as Linchpin of World Trade', 'Winners and Losers in the Global Silver Trade', and 'Birth of Globalization Debate: Ecological, Economic, Epidemiological, and Demographic Interactions'